Juridical Study of Movement #2019GantiPresiden in Election Crime Perspectives in Indonesia - Lestari, Sri Bayu Puji; Apriliani, Desi (Law Research Review Quarterly, 2018)
Measuring success in a democratic country, elections have their own significance. This is because holding direct elections can be a source of legitimacy for power in a country. Aside from being a source of legitimacy, this general election is one of the means to collect the political rights of every citizen. With the change of power through the electoral process, it is expected to bring leaders who are able to accommodate the ideals of the nation. As one of the stages procedures in the general election process carried out in Indonesia based on Undang-undang nomor 7 tahun 2017 tentang Pemilihan Umum, namely the campaign process. The campaign process is one of the strategic steps in the electoral stage to introduce the vision and mission as well as seeking public support for each candidate leader. Hastag #2019GantiPresident is a growing trend in Indonesia in 2019. This movement is one of the initiated by the opposition party with the aim of socializing its desire to replace the present president with a new president in the 2019 general election. in the democratic process, the campaign limits in the electoral law are determined. One of them relates to the campaign carried out outside the schedule set by the General Election Commission in the Regulation of the General Election Commission.